2010
DOI: 10.1111/j.1744-7976.2009.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Partial and Complete Adoption of Organic Farming Practices in Saskatchewan, Canada

Abstract: "Using a sample of organic producers in Saskatchewan, Canada, this study uses a Tobit model to identify the factors that discourage or encourage the complete adoption of organic farming and to assess why farmers differ in the share of total cultivated crop area they allocate to organic practices. In particular, the study evaluates the effect of transaction costs on the decision to convert partially or completely from conventional to organic practices. The results highlight the importance of lowering certain tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 30 publications
4
70
1
Order By: Relevance
“…Thus, the evidence of the positive effect of education on attitudes toward organic farming is indisputable. The findings of this study are, however, inconsistent with that of Cukur [13] and Khaledi et al [32]. The literature review has a unanimous agreement with respect to the assertion that larger households have a better attitude toward organic farming in comparison to smaller households [11,18,34].…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…Thus, the evidence of the positive effect of education on attitudes toward organic farming is indisputable. The findings of this study are, however, inconsistent with that of Cukur [13] and Khaledi et al [32]. The literature review has a unanimous agreement with respect to the assertion that larger households have a better attitude toward organic farming in comparison to smaller households [11,18,34].…”
Section: Resultscontrasting
confidence: 56%
“…In contrast to these studies, [13,32] show that the education levels of farmers have been found to have no significant effect on the probability of adopting organic farming practices. According to previous studies, organic farming has a greater need for labour in comparison to conventional farming [33].…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…This implies that the farm size decreases the tendency of adopting EFF by 0.80. Our finding supports the previous study by Khaledi et al [29] who found that farmers with smaller farmland can more easily manage their fields to certified regulations. In addition, relatively small farmlands could be easier to manage within the regulations and standards of organic farming.…”
Section: Factors Influencing the Adoption Of Partially Converted Farmsupporting
confidence: 83%
“…They are social dimension, including human relationship in the rural, health and environmental reasons. There are examples of some studies relating rural vitality (Mzoughi, 2011;Lasley et al 1993;Bird et al 1995), advancement of human skills on problem-solving and self-reliance which can mobilize local community (Flora, 1995), more community involvement (MacKinnon 2006), as well as health and environmental concerns (Bryne et al, 1991;Koesling et al, 2008;Padel, 2001;Hanson et al,2004;Stofferahn, 2009;Khaledi et al, 2010) However, there were studies suggesting that profit motives were stronger than environmental motives (Carr & Tate, 1991;Newman et al, 1990). Therefore, concerning merely social and environmental attitude may not enough for the continuation of organic farming.…”
Section: Literature Reviewmentioning
confidence: 99%